Preparation and Pharmacokinetic Characterization of an Anti-Virulence Compound Nanosuspensions - Nan Wang; Feng Qi; Xiaolong He; Honglan Shi; David W. Anderson; Hao Li; Hongmin Sun (MDPI AG, 2021)
Antibiotic resistance has become a worldwide public health threat due to the rapid evolution and spread of antibiotic-resistant bacteria. CCG-211790 is a novel anti-virulence compound that does not kill bacteria but could ameliorate human diseases by inhibiting expression of virulence factors, thereby applying less selection pressure for antibiotic resistance. However, its potential clinical use is restricted because of its poor aqueous solubility, resulting in formulation challenges. Nanosuspension technology is an effective way to circumvent this problem. Nanosuspensions of CCG-211790 with two different particle sizes, NanoA (315 ± 6 nm) and NanoB (915 ± 24 nm), were prepared using an antisolvent precipitation-ultrasonication method with Tween 80 as the stabilizer. Particle and pharmacokinetics (PK) of CCG-211790 nanosuspensions were characterized. Both NanoA and NanoB demonstrated remarkable increases in dissolution rate compared with the bulk compound. The PK parameters of NanoA were comparable to those of CCG-211790 solution formulation in intravenous or oral administration, suggesting that CCG-211790 nanosuspensions with smaller particle size improved oral bioavailability and drug exposure compared to traditional formulations of drug candidates.